Perubahan Perilaku Pemuda: Analisis Teori Kurt Lewin Dalam Konteks Keaktifan Pemuda Dalam Gereja (International Forum of Researchers and Lecturers, 2025)
Youth are an important resource for church development, but youth face challenges in maintaining a balance between spiritual and material life, where behavioral changes are influenced by the environment, technology, and lack of involvement in church services. The purpose of this article study is to analyze how youth behavior changes: analysis of Kurt Lewin's theory in the context of youth activity in the church. The method used is a literature study by using scientific literature as a data collection tool. Each data that has been collected will be analyzed reductively through information filtering, organizing, and summarizing the discussion.The research results show that,ChangeThe behavior experienced by Christian Youth affects their activeness in church service. The behavioral theory offered by Kurt Lewin is a solution to analyze behavioral changes in Christian youth. The three stages of behavioral theory in answering this problem areUnfreezingnamely the factors causing changes in the behavior of Christian Youth, including the environment, social media, family and church; Change (Movement) namely the strategy used to overcome changes in the behavior of Christian Youth, includingThe church can involve young people in various aspects of service, the church can provide a special forum for young people to develop their leadership, empowerment can be done through the involvement of young people in social services that are directly related to the community, the church can utilize social media and technology as a means to involve young people in service; Refreezing is an effort to implement strategies for Christian Youth, including instilling a good understanding of ethics and continuing to be in a positive community.